Women in the Holocaust - ʿOfer, Dalyah 1939-; Weitzman, Lenore J. (Yale University Press, 1998)
Introduction : the role of gender in the Holocaust / Lenore J. Weitzman and Dalia Ofer -- Gender and the Jewish family in modern Europe / Paula E. Hyman -- Keeping calm and weathering the storm : Jewish women's responses to daily life in Nazi Germany, 1933-1939 / Marion Kaplan -- The missing 52 percent : research on Jewish women in interwar Poland and its implications for Holocaust studies / Gershon Bacon -- Women in the Jewish labor bund in interwar Poland / Daniel Blatman -- Ordinary women in Nazi Germany : perpetrators, victims, followers, and bystanders / Gisela Bock -- The Grodno Ghetto and its underground : a personal narrative / Liza Chapnik -- The key game / Ida Fink -- 5050